THE IMPACT OF ORGANIZATIONAL COMMITMENT ON KNOWLEGDE SHARING - Demirel, Yavuz; Goc, Kubilayhan (European Scientific Journal, ESJ, 2013)
The main purpose of this study is to determine the relationship between employees’ knowledge sharings and commitment of the organization. For this purpose, a research has been done on a total of 537 employees who work in two private textile companies. Knowledge sharing in this study is defined as an activity which is mutual exchange knowledges such as information, talent or expertise within people, friends, family members, in a community or an organization. In accordance with this framework as the dimensions of knowledge sharing are treated as organizational and individual reasons that prevent knowledge sharing, individual and organizational results of knowledge sharing and finally individual and managerial perspectives in knowledge sharing. Organization commitment is treated as " individual’s identification with organization, participation in activities of organization and display of willingness, desire and power of effort in these subjects. In this research dimensions of organizational commitment, emotional commitment, continuance commitment and normative commitment are investigated. As a result of the research it has been revealed that organizational commitment and especially emotional commitment have positive effect on the exchange of information. As a result of this, organizations use their current resources more efficiently, they provide being stable and loyal of employees by generating of intraorganizational knowledge sharing culture. Besides, it is provided that increasing and protection of organization’s intellectual capital of employees by converting the knowledge of employees into organizational knowledge.